Perbandingan Gerakan Boycott, Divestment, Sanctions (BDS) Malaysia dan Indonesia sebagai Perlawanan terhadap Agresi Israel di Palestina - Inayah, Astiwi; Darmastuti, Ari; Simbolon, Khairunnisa; Latifa, Astritia (Universitas Syiah Kuala, 2025)
The Boycott, Divestment, Sanctions (BDS) is a global movement that aims to end international support for Israeli aggression against Palestinians and pressure Israel to comply with international law. This movement targets companies and products closely connected to Israeli violations, as any business relations with them are considered direct support for Israeli aggression against Palestine. Indonesia and Malaysia, as two Muslim majority countries in Southeast Asia, demonstrate their solidarity with the Palestinian people through the BDS Movement. This study employs a comparative method to examine similarities and differences in the implementation of the BDS Movement in both countries. The analysis is guided by the Transnational Advocacy Network (TAN) theory to explain the role of networks, framing strategies, and mobilization in shaping each country's BDS efforts. The purpose of this study is to describe the implementation of the BDS Movement in Malaysia and Indonesia, as well as to compare its dynamics, challenges, and impacts in the two contexts. The results of this study indicate that the Indonesian public remains selective in implementing the BDS Movement, while the Malaysian public has been more consistent in their actions. The study also finds that the BDS Movement in Malaysia has had a substantial impact on companies, resulting in stock declines, whereas in Indonesia, the movement has had a more direct effect on employees of the boycotted companies, who are vulnerable to layoffs.